Positive Modulators of the N-Methyl-d-aspartate Receptor: Structure-Activity Relationship Study of Steroidal 3-Hemiesters - Krausova, Barbora; Slavikova, Barbora; Nekardova, Michaela; Hubalkova, Pavla; Vyklicky, Vojtech; Chodounska, Hana; Vyklicky, Ladislav; Kudova, Eva (Journal of medicinal chemistry, 2018)
Here, we report the synthesis of pregn-5-ene and androst-5-ene dicarboxylic acid esters and explore the structure-activity relationship (SAR) for their modulation of N-methyl-d-aspartate receptors (NMDARs). All compounds were positive modulators of recombinant GluN1/GluN2B receptors (EC50 varying from 1.8 to 151.4 μM and Emax varying from 48% to 452%). Moreover, 10 compounds were found to be more potent GluN1/GluN2B receptor modulators than endogenous pregnenolone sulfate (EC50 = 21.7 μM). The SAR study revealed a relationship between the length of the residues at carbon C-3 of the steroid molecule and the positive modulatory effect at GluN1/GluN2B receptors for various D-ring modifications. A selected compound, 20-oxo-pregnenolone hemiadipate, potentiated native NMDARs to a similar extent as GluN1/GluN2A-D receptors and inhibited AMPARs and GABAAR responses. These results provide a unique opportunity for the development of new steroid based drugs with potential use in the treatment of neuropsychiatric disorders involving hypofunction of NMDARs.
Keywords: modulátory membránového transportu; Allosteric Regulation; Steroids; HEK293 buňky; Structure-Activity Relationship; molekulární struktura; Molecular Structure; HEK293 Cells; molekulární modely; vztahy mezi strukturou a aktivitou; Models, Molecular; alosterická regulace; lidé; receptory N-methyl-D-aspartátu; konformace proteinů; Humans; pregnenolon; Protein Conformation; steroidy; Receptors, N-Methyl-D-Aspartate; Membrane Transport Modulators; Pregnenolone